2019
DOI: 10.1371/journal.pone.0218986
|View full text |Cite
|
Sign up to set email alerts
|

The contralateral kidney presents with impaired mitochondrial functions and disrupted redox homeostasis after 14 days of unilateral ureteral obstruction in mice

Abstract: In unilateral ureteral obstruction (UUO), both oxidative stress and mitochondrial dysfunction are related to cell death. The aim of this study has been to characterize profiles of enzyme antioxidant activities and mitochondrial functioning of the contralateral (CL) compared to UUO and Sham (false-operated) kidneys of Balb/c mice. Kidneys were resected 14 days after obstruction for immunohistochemical and cortical mitochondrial functioning assays. Antioxidant enzymes activities were investigated in mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…This mechanism is critical for regulating redox homeostasis in the kidney. In renal pathologies, Nrf2 is deactivated, leading to OS increase [60,61]. In the kidney, persulfides regulate blood pressure and sodium reabsorption.…”
Section: Figurementioning
confidence: 99%
“…This mechanism is critical for regulating redox homeostasis in the kidney. In renal pathologies, Nrf2 is deactivated, leading to OS increase [60,61]. In the kidney, persulfides regulate blood pressure and sodium reabsorption.…”
Section: Figurementioning
confidence: 99%
“…Previous studies have demonstrated that overexpression of DsbA-L has a renal-protective role against lipid-related kidney damage in DN 17 . In the current study, we initially induced DsbA-L in TGF-β1-treated BUMPT cells as well as in the kidneys of UUO mice and Ob patients, especially as the mitochondrion damage existed in the UUO model 27,28 ; we presumed that the expression of DsbA-L in kidney tubular injury was associated with the damage of mitochondrion damage (see Fig. 1 and Supplementary Fig.…”
Section: Discussionmentioning
confidence: 94%
“…In a previous study from our group, we found that tyrosine kinase receptor AXL is involved in the progression of renal fibrosis in a UUO murine model and that AXL inhibitor bemcentinib attenuates disease development 16 . Mitochondrial dysfunction and oxidative stress have been demonstrated to play a role in the pathogenesis of renal fibrosis in both, humans and animal models 24,25 . In this study, we investigated the effects of Axl‐inhibitor bemcentinib on mitochondrial dysfunction associated with renal fibrosis.…”
Section: Discussionmentioning
confidence: 95%
“…16 Mitochondrial dysfunction and oxidative stress have been demonstrated to play a role in the pathogenesis of renal fibrosis in both, humans and animal models. 24,25 In this study, we investigated the effects of Axl-inhibitor bemcentinib on mitochondrial dysfunction associated with renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%